22nd International Conference and Exhibition on Electricity Distribution (CIRED 2013) 2013
DOI: 10.1049/cp.2013.0673
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the enforcement of a time-of-use tariff to residential customers in Italy

Abstract: Flat tariff has always been the default condition for residential customers in Italy and only starting from July, 1st 2010, the Italian Authority for Electricity and Gas (AEEG) approved the entry into force of a mandatory time-of-use (ToU) tariff at two-part rate periods. In order to assess the impact of the tariff in the short and medium term among Italian customers, R.S.E. has started a research project on residential loads and demand, in collaboration and under the patronage of AEEG. The results of such ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 3 publications
(3 reference statements)
0
15
0
Order By: Relevance
“…This was a positive factor from the end users' point of view, and about 60% of the households involved indicated that they had shifted at least some of their consumption from the more expensive peak hours to cheaper off-peak hours. This resulted in a shift of 1% of total energy consumption from peak to off-peak hours with respect to the period prior to the introduction of the TOU tariff [29]. The CLNR project (Customer Led Network Revolution) in England also opted for a simple tariff scheme: a three-rate TOU tariff which is updated once a year.…”
Section: Resultsmentioning
confidence: 99%
“…This was a positive factor from the end users' point of view, and about 60% of the households involved indicated that they had shifted at least some of their consumption from the more expensive peak hours to cheaper off-peak hours. This resulted in a shift of 1% of total energy consumption from peak to off-peak hours with respect to the period prior to the introduction of the TOU tariff [29]. The CLNR project (Customer Led Network Revolution) in England also opted for a simple tariff scheme: a three-rate TOU tariff which is updated once a year.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the increased number of measurements allowed the activation of new services for customers such as the exploitation of ToU pricing regime with three time bands for households and small business customers [25], invoices on real consumption, remote contract management, together with network management (e.g., loss reduction) whose benefits can pass to the final customers thanks to the regulation.…”
Section: A Review Of Energy Metering Deployment Strategiesmentioning
confidence: 99%
“…The difference between peak and off-peak tariff must be significant or else it will not able to change the load profile as desired. This is the case of Time of Use tariff program in Italy [1]. From the study in [1], after the implementation of mandatory TOU program, they discovered about only 1% of peak shifting consumption occur from peak hour to off-peak hour.…”
Section: Time Of Use (Tou) Electricity Pricingmentioning
confidence: 99%
“…Time-of-Use (TOU) program have already been implemented throughout the world with different approach and mechanism [1][2][3][4][5][6]. Nevertheless they share the same ultimate goal of to stabilize the generation rate to meet up with the ever increasing consumer demand.…”
Section: Introductionmentioning
confidence: 99%